2018
DOI: 10.1016/j.pscychresns.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the neural correlates of psychological therapies in major depression

Abstract: Longitudinal neuroimaging studies in major depression have revealed cortico-limbic abnormalities which are modulated by treatment. We performed a systematic review and meta-analysis of psychotherapy treatment studies measuring neural function and metabolism using fMRI, PET, SPECT and MRS. Seventeen studies were included in the systematic review, total of 200 major depression participants (mean age 37.6 years), all medication free, and 116 healthy controls (mean age 36.4 years). Neuroimaging assessments were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(22 citation statements)
references
References 74 publications
0
19
0
1
Order By: Relevance
“…Using functional magnetic resonance imaging, we showed that 30 minutes of blue-wavelength light stimulation enhanced activation of the rostral anterior cingulate cortex (rACC) when participants were anticipating rewarding stimuli [12]. This brain region is important for expectations of pleasure [13] and is often reduced in volume in patients with depression [14]. Light appears to activate many of these positive emotion and cortical alerting systems almost immediately upon exposure [15,16].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Using functional magnetic resonance imaging, we showed that 30 minutes of blue-wavelength light stimulation enhanced activation of the rostral anterior cingulate cortex (rACC) when participants were anticipating rewarding stimuli [12]. This brain region is important for expectations of pleasure [13] and is often reduced in volume in patients with depression [14]. Light appears to activate many of these positive emotion and cortical alerting systems almost immediately upon exposure [15,16].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…77 Our meta-analysis of longitudinal treatment effects after psychotherapy found a significant group by time effect in the left rostral anterior cingulate in response to emotional stimuli, in which MDD participants showed increased activity following treatment while healthy participants showed a decrease in activity at the follow-up scan. 78 Ventral-rostral regions in the anterior cingulate have a regulatory function on emotion processing, as well as in reward processing and decision making, through interconnections with core emotion processing regions, in particular the amygdala. 79 MDD is associated with a bias toward negative affective valences, which is also evident in a decreased ability to disengage from negative stimuli.…”
Section: Systems and Neuroplasticitymentioning
confidence: 99%
“…Modern neuroscience is increasingly providing the crucial data to bridge this divide and to demonstrate the nuanced ways in which bio-, psycho-, and social processes are all mediated through the brain. For example, a large body of literature has demonstrated the ability of psychotherapy to alter brain activity in a way that promotes improved emotional regulation 7 . Early social experiences, such as a history of abuse and/or neglect, can blunt the brain's response to rewards in the environment (such as money or social praise), while increasing sensitivity to drugs of abuse 8,9 .…”
Section: Haunted By Descartes' Ghostmentioning
confidence: 99%